2020
DOI: 10.3389/fgene.2020.565006
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences of Photosynthesis Establishment Related mRNAs and Novel lncRNAs in Early Seedlings (Coleoptile/Cotyledon vs. True Leaf) of Rice and Arabidopsis

Abstract: Photosynthesis uses sunlight and carbon dioxide to produce biomass that is vital to all life on earth. In seed plants, leaf is the main organ for photosynthesis and production of organic nutrients. The seeds are mobilized to fuel post-germination seedling growth until seedling photosynthesis can be efficiently established. However, the photosynthesis and metabolism in the early growth and development have not been studied systematically and are still largely unknown. In this study, we used two model plants, ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Previous works have already established the relationship between lncRNAs and processes related to photosynthesis in A. thaliana and rice [134], as well as in the response to different types of light [18,135]. Photosynthesis is arguably the most important biological pathway in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have already established the relationship between lncRNAs and processes related to photosynthesis in A. thaliana and rice [134], as well as in the response to different types of light [18,135]. Photosynthesis is arguably the most important biological pathway in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous study showed that long-chain non-coding RNAs (lncRNAs) might participate in the carbohydrate metabolism. Shi et al (2020) reported that some lncRNAs is related to the expression regulation of key genes in starch and sucrose metabolisms, which participate in seedling development in rice and Arabidopsis. Although previous studies have shown that carbohydrates play an important role in post-mowing regeneration of wheat, the expression patterns of key genes and the changes in carbohydrate metabolism during this process remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The establishment process of photosynthetic machinery during young seedling development from the time of germination is still not fully understood. Recently, photosynthesis establishment early in seedling growth has been compared between rice (monocotyledonous) and Arabidopsis (dicotyledonous), wherein photosynthesis in the monocot model establishes gradually from the coleoptile to the first leaf, but in the dicot model photosynthesis is welldeveloped in the cotyledons and maintains at a similar level throughout seedling development (Shi et al, 2020). Our gene expression study of maize seedlings, which are also monocotyledonous, are similar to observations in rice in that the up-regulation of photosynthesisrelated genes commences once the seedlings emerge above ground and continues in the leaves that sequentially develop from the shoot meristem.…”
Section: Developmental Cues Enhance Cuticle Depositionmentioning
confidence: 99%